Direito líquido: uma análise da materialização do estado de liquefação da estrutura jurídica nacional - Ferreira Pipino, Marina Beatriz (2022)
The objective of the present work is to highlight and analyze how scientific and technological development affected the national legal framework. Law is the matter chosen to establish the rules and other archetypes of social functioning. As an inherent part of society, the law reflects in its determinations the changes that society is experiencing. In the current perspective, as well as society, the law has undergone significant transformations as a result of the scientific and technological development that affected its structure, generating the following question: if the law is an inherent part of society and society has been modified by modernity, being in a state of liquefaction, then the law and its legal structure were also modified, being in the liquefaction phase. What characteristics of modernity would be present infiltrating the Brazilian legal structure? How is the national legal framework liquefying? The CTS field is an interdisciplinary area of study that brings society, science and technology together. In this way, the CTS field presented itself as the most fertile field for us to establish communication in order to analyze how scientific and technological development affected the national legal structure, answering our guiding questions. Within this field, Bauman's work “Modernidade Líquida” was the theoretical framework listed to scrutinize the inquiries, which in the end revealed the materialization of liquidity in the national legal structure. In order to reach the purpose of answering the questions and verifying at what point liquid modernity affected national law, we apply the complex methodology proposed by Morin (2004) which infers that it is not possible to think about knowledge in isolation, it is necessary to think about it in an isolated way. interdisciplinary. Together, the methodological procedures of bibliographic, historical, documentary and comparative review were also applied.